(untitled) (Sains Humanika, 2014)
The purpose of this study is to examine the relationship between career development practices and high performance talent. Particularly, the objectives of this study were (1) to identify the career development practice in selected service organization; (2) to examine the talent’s perception in regards to career development practice in the organization; (3) to identify the talent’s perception in regards to their current performance; (4) to study the relationship between succession planning, job rotation, pipeline system, mentoring program, educational and tuition reimbursement practices toward developing high performance talent; (5) to determine the relationship between overall career development practices and high performance talent. This study utilized theory developed by Gutteridge (1993), Holstein (2005) and Super (1954). Data were collected by both qualitative and quantitative methods. Focus group discussion with 15 selected Human Resource Manager was initially conducted to help the researchers to develop the survey questionnaire. A number 233 respondents from three selected organizations namely aviation, postal service and manufacturing involved in the survey. Qualitative data were analyzed using thematic analysis. Both descriptive and inferential statistics namely frequency, mean, and Pearson correlation were used to analyze the quantitative data. Results of focus group discussion found that among the career development practices that were practiced in their organizations are job rotation, mentoring, pipeline system, succession planning and education tuition fees reimbursement. Results of that correlation analysis showed a significant relationship between educational and tuition reimbursement, job rotation, mentoring program, pipeline system, succession planning and high performance talent ranges from moderate to strong relationship. The results also showed that overall career development practices was significantly correlated with high performance talent. Lastly, recommendations for practices and future studies were also discussed.